The Lysholm score: Cross cultural validation and evaluation of psychometric properties of the Spanish version. - Arroyo Morales, Manuel; Martín-Alguacil, José; Lozano-Lozano, Mario; Cuesta-Vargas, Antonio; Fernández-Fernández, Andrés J.; González, José A.; Tegner, Yelverton; Cantarero-Villanueva, Irene (PLoS One, 2019)
Background: This study aims at assessing the validity and reliability of the Spanish version of the Lysholm score, a widely used instrument for assessing knee function and activity level after ligament injuries. Methods: Ninety-five participants (67.4% male, 22±5 years) completed the questionnaire twice within 7 days and a subsample of 42 participants completed a test-retest reliability. Reliability, validity and feasibility psychometric properties were studied. The validity of the questionnaire was analysed using ceiling and floor effects. Factor structure and construct validity were analysed with the SF-36, the Hip and Knee Questionnaire (HKQ) and one leg jump test (OLJT). Results: Criterion validity with the SF-36 Physical State was moderate (r = 0.50 and p<0.01), poor and inverse relationship (r = -0.31, p<0.01) with HKQ and positive moderate (r = 0.59, p<0.01) with OLJT. Measurement error from MDC90 was 3.9%. Exploratory factor analysis demonstrated a one-factor solution explaining 51.5% of total variance. The x2 test for the one-factor model was significant (x2 = 29.58, df = 20, p < 0.08). Test-retest reliability level was high (ICC2.1 = 0.92, p<0.01) and also the internal consistency (α = 0.77). Conclusion: The Spanish Lysholm score demonstrated that it is a reliable and valid instrument that can be used to assess knee function after ligament injuries.
Keywords: Personas con discapacidad - Evaluación funcional; Psicometría; Disability evaluation; Surveys and questionnaires; Psychometric properties; Evaluation